Millennial loyalty towards artificial intelligence-enabled mobile banking: evidence from Indonesian Islamic banks. Issue 9 (14th July 2021) - Suhartanto, Dwi; Syarief, Moch Edman; Chandra Nugraha, Ade; Suhaeni, Tintin; Masthura, Ambia; Amin, Hanudin
Abstract : Purpose: This study aims to examine factors driving millennial loyalty towards artificial intelligence (AI)-enabled mobile banking services in Islamic banks. Design/methodology/approach: This research collected the data from 204 millennial customers of Islamic banks in Aceh, Indonesia. Partial least square (PLS) was used to evaluate the effect of service factors (the need for service and service quality), technology-based factors (attitudes towards AI, relative advantage, security and trust) and religiosity on millennial loyalty towards AI-enabled mobile banking. Findings: This inquiry reveals that service quality, attitude towards AI and trust are determinants important for millennial loyalty towards AI-enabled mobile banking. Further, this research notes the significant role of religiosity on millennial loyalty towards mobile banking services. Practical implications: This study suggests Islamic banks focus on developing millennial trust and attitude towards AI to increase their loyalty towards AI-enabled mobile banking services. Further, Islamic banks operation that complies with Islamic law is strongly suggested to develop millennial loyalty. Originality/value: To the best of the authors' knowledge, this is the first study that tries to scrutinize loyalty towards AI-enabled mobile banking.